Evaluation of the Operational Performance of the Telaga Punggur Ferry Port in Riau Islands Province - Khairani, Muhammad; Agustina, Elfita; Putra, Padi Gemilang; Mu'tamar, Rispa Saeful (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2025)
Telaga Punggur Ferry Port, as a class I port in the Riau Islands Province, plays a strategic role in passenger and vehicle mobility. This study aims to evaluate the port's operational performance based on five indicators in accordance with the Decree of the Director General of Land Transportation Number KP-DRJD 539 of 2022. The method used is descriptive quantitative through surveys and observations for 10 days in March 2025. The results show an average ship maneuvering time of 8.17 minutes (sufficient category), vehicle boarding time of 1.21 minutes and disembarking time of 2.06 minutes (good), and vehicle queuing time of 76 minutes 44 seconds (very poor) with the longest queue of 4 hours 30 minutes. The Berth Occupancy Ratio value shows that pier 1 (sufficient) and pier 2 (very good). It is concluded that operational performance still needs to be improved, especially in vehicle queue management and pier utilization. Recommendations include increasing operator supervision, improving infrastructure, adjusting ship frequencies, and optimizing the ticketing system and ship schedule coordination.